Access of new systemic therapies for Genito-urinary cancers in low-middle income countries - Herchenhorn, Daniel; Freire, Vinicius (Frontiers in Urology, 2022)
The availability of new systemic therapies associated with better outcomes and survival for GU tumors is a major obstacle for most LMIC. Strategies to improve access are necessary and depend not only on drug availability, but from public health care system organization, discussion and priorities as well as strategies to decrease cost by rational treatment decision and individualize use of systemic therapies in limited resource countries. Efforts should be implemented to provide more real-world data coming from LMIC and studies focusing in strategies to decrease drug costs are urgently needed.